4D dosimetry and motion management in clinical radiotherapy. (August 2019) - Bäck, S Å J; Franich, R D; Edvardsson, A; Ceberg, S
Abstract: Many novel modulated radiation treatment techniques are sensitive to patient motion which may degrade the dose distribution considerably. As there may be a simultaneous movement of the tumour and treatment machine, undesired heterogeneities in the dose distribution can be resulted. Methods to estimate the dosimetric effect of motion and treatment deliveries for both photons and protons are needed. We have recently studied Hodgkin's lymphoma, liver and left sided breast cancer cases and developed tools to be able to simulate simultaneous organ movement and treatment delivery. Furthermore, it is of great importance to validate potential simulations in a realistic quality control set-up, ideally including a complete dosimetry volume and movement/deformation (4D). Radiation sensitive deformable gels have the potential to meet this dosimetry challenge owing to the unique 3D characteristic to form both phantom and detector in one volume. Multi-array detectors together with a moving platform and a realistic object trajectory is an alternative to evaluate the clinical setting. The evaluation could then in principle be done on-line. Gel/plastic 3D dosimeters have the potential to also be irradiated during motion in a similar matter but have to be read-out post irradiation.